Fundraising Product Innovation of BMT Mandiri Artha Sejahtera in the Covid-19 Pandemic Period - Anisah, Ana Nur; Purnomo, Joko Hadi; Hidayati, Niswatin Nurul (SHAHIH: Journal of Islamicate Multidisciplinary, 2021)
This research aimed to find out how to innovate BMT Mandiri Artha Sejahtera fundraising products during the Covid-19 pandemic. This research used qualitative research and the analysis was carried out by Data Reduction, Data Display, and finally Conclusion Drawing/verification. This research used data collection methods through interviews, observation, and documentation. Fundraising product innovations carried out by BMT Mandiri Artha Sejahtera during the Covid-19 pandemic included two aspects, they were innovation in services and products. In service innovation, BMT MAS innovated the system by using a mobile printer. The use of this tool makes transaction activities less time-consuming so as to prevent crowds between members, marketing staff and buyers in the Sumberrejo and Kapas markets. Practical and easy services make member satisfaction achieved and keep saving. In product innovation, BMT MAS uses an imitation strategy from the BMT BUS product that has been introduced to members. Then BMT MAS developed its product with a mutation strategy.